2012
DOI: 10.1007/s00373-012-1169-8
|View full text |Cite
|
Sign up to set email alerts
|

A Note on 5-Cycle Double Covers

Abstract: The strong cycle double cover conjecture states that for every circuit C of a bridgeless cubic graph G, there is a cycle double cover of G which contains C. We conjecture that there is even a 5-cycle double cover S of G which contains C, i.e. C is a subgraph of one of the five 2-regular subgraphs of S. We prove a necessary and sufficient condition for a 2-regular subgraph to be contained in a 5-cycle double cover of G.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…In a common refinement of the strong CDCC and the 5-CDCC one may ask whether any cycle is part of some 5-CDC. In [29] Hoffmann-Ostenhof gives the following characterization of 2-regular subgraphs which can be part of a 5-CDC: Theorem 6.4 (Hoffmann-Ostenhof [29]). Let G be a cubic graph and D be a 2-regular subgraph of G. Then there is a 5-CDC which contains D if and only if G contains two 2-regular subgraphs D 1 and D 2 such that D ⊂ D 1 , M = E(D 1 ) ∩ E(D 2 ) is a matching and G − M has a nowhere-zero 4-flow.…”
Section: Oriented Cycle Double Covers and K-cdcsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a common refinement of the strong CDCC and the 5-CDCC one may ask whether any cycle is part of some 5-CDC. In [29] Hoffmann-Ostenhof gives the following characterization of 2-regular subgraphs which can be part of a 5-CDC: Theorem 6.4 (Hoffmann-Ostenhof [29]). Let G be a cubic graph and D be a 2-regular subgraph of G. Then there is a 5-CDC which contains D if and only if G contains two 2-regular subgraphs D 1 and D 2 such that D ⊂ D 1 , M = E(D 1 ) ∩ E(D 2 ) is a matching and G − M has a nowhere-zero 4-flow.…”
Section: Oriented Cycle Double Covers and K-cdcsmentioning
confidence: 99%
“…In the same paper he conjectured that not only can every cycle be included in some CDC but it can in fact always be part of some 5-CDC. Conjecture 6.5 (Hoffmann-Ostenhof [29]). Every cycle C in a bridgeless cubic graph G is contained in some 5-CDC of G.…”
Section: Oriented Cycle Double Covers and K-cdcsmentioning
confidence: 99%
See 1 more Smart Citation
“…G in Corollary 4.3 has some CDC even if C is separating, see [10]. The above results offer some insight which cycles are part of a 5-CDC, see the Strong 5-CDCC in [14].…”
Section: Proofmentioning
confidence: 85%
“…As an approach toward proving the CDCC Goddyn suggested that every circuit in a bridgeless cubic graph could be used to start a CDC (this is commonly referred to as the strong cycle double cover conjecture, SCDCC), and proved this for the Isaacs snarks. In view of this and Celmins' 5CDCC, Hoffmann‐Ostenhof conjectured in his PhD thesis at the University of Vienna and in that every circuit in a bridgeless cubic graph can be used to start a 5CDC. This conjecture (S5CDCC) has been proven by a computer search for graphs with at most 34 vertices and for all cyclically 5‐edge connected snarks on 36 vertices, as reported in and .…”
Section: Introduction and Preliminary Discussionmentioning
confidence: 95%